SHOPPING HABITS, FASHION PREFERENCES,ETHICAL CONSUMPTION (Ustozlar uchun, 2025)
This article explores the complex intersection of modern consumer shopping habits, individual fashion preferences, and the burgeoning movement toward ethical consumption within the global apparel industry. The study first analyzes the prevalence of the Fast Fashion business model, which relies on cheap production and frequent consumption, contrasting it with contemporary digital shopping trends, where social media and convenience drive purchasing decisions. A central focus is placed on understanding the symbolic nature of fashion, where clothing choices serve as a “second skin” and reflect self-identity and personal values.